Enhancing Children's Group Cooperation Through the RUBIKONS (Guidance and Counseling House) Program - Nurcahyani, Sabbila; Saputri , Badriani; Alridho Lubis , Muhammad (Jurnal Karya Abdi Masyarakat, 2023)
Character education plays a vital role in shaping children's attitudes, personalities, and values. One key element of character education is the ability to cooperate, a skill that should be nurtured from an early age to support children's social development and integration within their communities. This community service initiative introduces the RUBIKONS (Guidance and Counseling House) program, developed by counseling and guidance students, as a platform for enhancing children’s social-emotional skills through a combination of non-formal education and psychoeducational activities. The project employed a Participatory Action Research (PAR) approach, emphasizing cooperation between researchers and community stakeholders. The main partner in this initiative was the Ulu Gedong Subdistrict Office, which served as the institutional supporter and coordinator. The program targeted children aged 6–13 years and involved a series of structured group activities designed to foster teamwork and cooperative behavior. Results indicated a notable improvement in the children's ability to cooperate effectively within group settings. This initiative highlights the potential of structured psychoeducational interventions to support character education and social development in community-based settings.